Navigating the Rise of Smart Tourism: Implications of Technology and Data for Sustainable Industry Growth - Hoang, Hien; Trang, Pham Huong (Sociology Department, Brawijaya University, 2023)
This paper explores the complex landscape of smart tourism, investigating the implications of technology and data for sustainable growth within the tourism industry. Understanding the nuanced interplay between smart tourism initiatives and sustainability has become critical as the sector undergoes a paradigm shift driven by technological advancements. The paper contextualizes the emergence of smart tourism, unraveling the pivotal role of technology and data in transforming industry dynamics. Through comprehensive analysis, it examines how cutting-edge technologies including artificial intelligence, big data analytics, and the Internet of Things shape diverse aspects of tourism, from customer experience to operational efficiency. Additionally, it synthesizes evidence on the benefits of smart tourism for enhancing efficiency, sustainability, inclusiveness, experiential quality, and competitiveness across the sector. In conclusion, it contemplates future applications while underscoring the need for a balanced integration of technology and data to realize the promise of smart tourism. Further research on emerging applications, challenges, and best practices is highlighted to guide destinations towards this technology-enabled yet sustainable future.